Debates on Theories of Art: A Case of a Cluster Account - Radeev, Artem E. (Actual Problems of Theory and History of Art, 2020)
The article deals with the cluster account of art, which became widespread in the beginning of the 21st century. This account is notable both by the fact that it has caused a series of debates about what art isand by the fact that the cluster account clarifies some features of these debates. The article describes how the cluster account works but also provides arguments against this account. The author has attempted to reveal the meaning of the statement that there are no necessary and sufficient conditions for an object to be referred to as a work of art; he determines what criteria allow to make a cluster of a particular concept of art, reveals what new such cluster account may bring to the theory of art. The article also makes a more general conclusion about what the idea of clustering in the approach to art is based upon.